DETERMINATION OF BACKWARDS RATE CONSTANT AND EQUILIBRIUM CONSTANT USING IRREVERSIBLE APPROACH AND FORWARD RATE LAW - Patiha, Patiha (Alchemy Jurnal Penelitian Kimia, 2013)
A determination technique of backward rate constantÂ kbÂ and equilibrium constantÂ KÂ using irreversible reaction approach and forward reaction rate law has been introduced. The rate law of backward reaction was determined from the integral equation that produced the smallest standard deviation of the average value of rate constant,Â k.Â These rate constants were calculated based on the difference of the concentration of products observed at various definited times to the concentration that should present if the forward reaction is irreversible. The backward rate constant,Â kbÂ is the rate constant which is calculated at the beginning of the observation. Â Then, in combination with theÂ kfÂ Â value which was obtained from the forward rate law, the equilibrium constant, K, could be calculated. This technique was then tested on data of a first-order reversible reaction, on both directions. Those data were taken from Wright (2004) and Wilkinson (1980).The validity was determined based on the suitability of the values (with a tolerance of differences â¤Â 5%) ofÂ kbÂ andÂ KÂ which are given by Wright (2004) and Wilkinson (1980). The resultsÂ showÂ that theÂ techniqueÂ isÂ valid.